2017
DOI: 10.1016/j.yhbeh.2017.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Prosocial effects of prolactin in male rats: Social recognition, social approach and social learning

Abstract: Prolactin (PRL) and oxytocin (OT) are pituitary hormones essential for lactation, but also promote sexual behavior. OT stimulates social behaviors, such as recognition, approach, and learning, but less is known about PRL in these behaviors. Since PRL and OT have complementary functions in reproduction, we hypothesized that PRL increases social recognition, approach, and learning. Male Long-Evans rats received ovine PRL (oPRL; 0.5, 2.0 or 5.0 mg/kg), the PRL antagonist bromocriptine (0.1, 3.0 or 5.0 mg/kg) or s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…Furthermore, correlative studies in birds and mammals have revealed associations of prolactin with social and cooperative behaviours (Schoch et al 1996;Carlson et al 2006;Smiley and Adkins-regan 2016;Donhoffner et al 2017). Male birds and mice show higher levels of prolactin if they invested in parental care (Schradin 2008a;Angelier and Chastel 2009), prolactin affects the decision to babysit in meerkat (Suricatta suricatta) helpers (Carlson et al 2006) and increases social recognition in rats (Donhoffner et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, correlative studies in birds and mammals have revealed associations of prolactin with social and cooperative behaviours (Schoch et al 1996;Carlson et al 2006;Smiley and Adkins-regan 2016;Donhoffner et al 2017). Male birds and mice show higher levels of prolactin if they invested in parental care (Schradin 2008a;Angelier and Chastel 2009), prolactin affects the decision to babysit in meerkat (Suricatta suricatta) helpers (Carlson et al 2006) and increases social recognition in rats (Donhoffner et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These results parallel our findings in the hypothalamus of females, which may be an indication that females with small social network sizes are dominant to females with large ones, even outside of the reproductive season. Some of these effects could be exerted through the pituitary hormone prolactin, as a critical function of dopamine released from the hypothalamus is in the suppression of pituitary secretion of prolactin [ 51 ] and because, among its many functions [ 52 ], prolactin is associated with social behaviors in several taxa, including parental behaviors [ 53 , 54 ] and prosocial and affiliative behaviors [ 55 , 56 ]. In terms of pathways containing downregulated genes, the ones highlighted in our GO term enrichment analysis were mostly related to the regulation of the inflammatory response, and the genes repeatedly represented in those pathways were Snx4 and Cd47 .…”
Section: Discussionmentioning
confidence: 99%